(y-7)(y-7)(y-7)=6

Simple and best practice solution for (y-7)(y-7)(y-7)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y-7)(y-7)(y-7)=6 equation:


Simplifying
(y + -7)(y + -7)(y + -7) = 6

Reorder the terms:
(-7 + y)(y + -7)(y + -7) = 6

Reorder the terms:
(-7 + y)(-7 + y)(y + -7) = 6

Reorder the terms:
(-7 + y)(-7 + y)(-7 + y) = 6

Multiply (-7 + y) * (-7 + y)
(-7(-7 + y) + y(-7 + y))(-7 + y) = 6
((-7 * -7 + y * -7) + y(-7 + y))(-7 + y) = 6
((49 + -7y) + y(-7 + y))(-7 + y) = 6
(49 + -7y + (-7 * y + y * y))(-7 + y) = 6
(49 + -7y + (-7y + y2))(-7 + y) = 6

Combine like terms: -7y + -7y = -14y
(49 + -14y + y2)(-7 + y) = 6

Multiply (49 + -14y + y2) * (-7 + y)
(49(-7 + y) + -14y * (-7 + y) + y2(-7 + y)) = 6
((-7 * 49 + y * 49) + -14y * (-7 + y) + y2(-7 + y)) = 6
((-343 + 49y) + -14y * (-7 + y) + y2(-7 + y)) = 6
(-343 + 49y + (-7 * -14y + y * -14y) + y2(-7 + y)) = 6
(-343 + 49y + (98y + -14y2) + y2(-7 + y)) = 6
(-343 + 49y + 98y + -14y2 + (-7 * y2 + y * y2)) = 6
(-343 + 49y + 98y + -14y2 + (-7y2 + y3)) = 6

Combine like terms: 49y + 98y = 147y
(-343 + 147y + -14y2 + -7y2 + y3) = 6

Combine like terms: -14y2 + -7y2 = -21y2
(-343 + 147y + -21y2 + y3) = 6

Solving
-343 + 147y + -21y2 + y3 = 6

Solving for variable 'y'.

Reorder the terms:
-343 + -6 + 147y + -21y2 + y3 = 6 + -6

Combine like terms: -343 + -6 = -349
-349 + 147y + -21y2 + y3 = 6 + -6

Combine like terms: 6 + -6 = 0
-349 + 147y + -21y2 + y3 = 0

The solution to this equation could not be determined.

See similar equations:

| v+10=-1 | | 8316=(14784)r(9) | | 4x-6(2x-3)= | | -7+4m=-5+6m | | 8w-3/2=13-7w-1/8 | | 2/3y-1=7/9 | | 34-4-4b=18 | | 3-(x-4)=2x-6+5x | | 100/6x=79.49 | | 8+(-8)=16 | | 9(x-6)(x+1)=0 | | 5x+2(1-x)=2(2x-4) | | 6y-(y-2)=12/0.064/3 | | 9+v=-5 | | 4p^2-(2p^2-3p+1)= | | 11x-4=10x+5-6 | | x-5/8/2x-10/56 | | 3(x+4)-2(3x-5)+4x-1=4(2x-1)-(2x+5) | | 2x^2=7200 | | 79.49=100/6x | | -7x-27=8-1(1x-19) | | X/9=14/18 | | q^7-9q^5=0 | | ab-4a-4b+8=0 | | 5a+(-7)=-2 | | 4k-7+16=-3 | | 5x+20=24-3x-12 | | 7/(9-5i) | | 2x-4=3(-8-4x) | | 8-3x-(2x-4)=-3 | | (x^2y^3)/xy^4 | | 11/21*42 |

Equations solver categories